2019
DOI: 10.1016/j.ijhydene.2018.08.145
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of energy generation efficiency in industrial facilities by SOFC – SOEC systems with additional hydrogen production

Abstract: Industry is one of the highest energy consumption sector: some facilities like steelworks, foundries, or paper mills are highly energy-intensive activities. Many countries have already implemented subsidies on energy efficiency in generation and utilisation, with the aim of decreasing overall consumption and energy intensity of gross domestic product. Meanwhile, researchers have increased interest into alternative energy systems to decrease pollution and use of fossil fuels. Hydrogen, in particular, is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The S‐CO 2 /T‐CO 2 system is capable of chilling the refrigerated truck examined adequately. Vialetto et al 28 demonstrated the increased power generation performance in industrial installations using SOFC/solid oxide electrolysis cell (SOEC) combinations along with extra hydrogen generation. The study analyzed the re‐engineering of a paper mill's energy production system.…”
Section: Introductionmentioning
confidence: 99%
“…The S‐CO 2 /T‐CO 2 system is capable of chilling the refrigerated truck examined adequately. Vialetto et al 28 demonstrated the increased power generation performance in industrial installations using SOFC/solid oxide electrolysis cell (SOEC) combinations along with extra hydrogen generation. The study analyzed the re‐engineering of a paper mill's energy production system.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the increased complexity of the system, results show savings of 2% to 6%. Hydrogen production was evaluated comparing the RSOC integrated system with proton exchange membrane (PEM) electrolysis in terms of primary energy and economics [3]. Ferronato N analyzes the main strengths and weaknesses of implementing a sustainable MSWM.…”
Section: Introductionmentioning
confidence: 99%
“…Solid oxide cells (SOCs) are being employed in a wide range of applications such as power generation, Power-to-X, and so forth [1][2][3][4][5][6]. These large-scale applications require long operational lifetimes, in the range of several 10 000 h. Lab and pilot-scale tests in these time scales have been carried out in the past [7][8][9].…”
Section: Introductionmentioning
confidence: 99%